Biomonitoring of atmospheric heavy metal pollution using lichens and mosses in the city of Istanbul, Turkey - (:unkn) unknown (My University, 2009)
This paper presents the analysis of air pollutants in naturally growing lichens and mosses sampled at 10 urban and suburban sites in the city of Istanbul, Turkey. Ten elements (Al, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Zn) were measured in the malli of eight lichen species (Cladonia spp., Evernia prunastri, Flavoparmelia caperata, Hypogymnia tubulosa, Parmelia sulcata, Physcia adscendens, Xantho-parmelia tinctina, Xanthoria parietina) and three moss species (Didymodon vinealis, Hypnum cupressiforme, Pylaisia polyantha) using Atomic Absorption Spectrometry (AAS). Based on the analysis of the lichen samples, the heavy metal concentrations from the highest to the lowest are as follows: Mn > Zn > Pb > Cu > Al > Ni > Cr > Fe > Co > Cd. The elemental composition of lichens and mosses can be used as biomonitor value to indicate air pollution levels in the city.
Keywords: Biomonitor; Istanbul; Lichen; Metals; Moss; Pollution